At the Lower End of the Table: Determinants of Poverty among Immigrants to Denmark and Sweden - Mette Verner; Peder J. Pedersen; Björn Gustafsson; Kræn Blume (Institute for the Study of Labor (IZA), 2005)
In this paper we study determinants of relative poverty among immigrants and natives in Denmark and Sweden during the 1980s and 1990s. Denmark and Sweden share the same properties in a range of labour market and welfare state characteristics. At the same time they differ very much in cyclical profiles and immigration experiences during recent decades. Both countries have followed the same principles regarding immigration policy, i.e. immigration from low income countries has been restricted to tied movers and refugees. We use 60 percent of the median in the distribution of equivalent disposable as poverty line. Data comes from two large panels based on administrative data. We find that immigrants have higher poverty rates than natives in both countries and that this difference has clearly increased in both countries. The paper reports results based on running probability models of poverty incidence. Explanatory variables include measures of years since immigration, demographic characteristics, and variables measuring country of origin. We conclude that a significant part of the difference in aggregate immigrant poverty rates reflect differences in composition by country of origin and differences in the structure of benefits to families with children.
Keywords: I32; J15; F22; 330; poverty; immigrants; panel data